Diez noches de Francisca Lombardo - Eltit, Diamela (Debate Feminista, 1991)
<span style="display: inline !important; float: none; background-color: #ffffff; color: #000000; cursor: text; font-family: Roboto,RobotoDraft,Helvetica,Arial,sans-serif; font-size: 13px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: pre-wrap; word-spacing: 0px; word-wrap: break-word;">Diez noches de Francisca Lombardo